Fatigue life estimation under multi-axial random loading in light poles - Kashyzadeh, Kazem Reza (Ciência e Natura, 2015)
In the present paper, fatigue life of light poles under multi-axial random loading based on the variable wind direction and speed has been studied. To achieve these purposes, light pole is simulated with all loading conditions in ABAQUS Software. To consider to the three storm days as the critical loading conditions, Random vibration analysis has been performed to obtain stress histories and equivalent stress. Finally, Calculate fatigue life of light pole by using Dirlik Theory.